Enhancing English Language Teaching: A Comprehensive Examination of Professional Development Needs Across Career Stages - Almuhammadi, Anas (International Journal of English Language Education, 2022)
This research delves into the professional development needs of English language teachers across various career stages, from novice to experienced educators. Utilizing focus group interviews, two distinct groups of teachers were engaged: novice and experienced teachers. The data collected through focus group interviews were analyzed using thematic analysis approach to achieve the study aim: uncover specific areas of professional growth crucial for effective teaching practices and student engagement. For novice teachers, the focus was on foundational teaching skills, including lesson planning, classroom management, and effective instructional strategies. Additionally, attention was given to language proficiency enhancement to facilitate better language learning experiences in the classroom. Mentorship and support programs were identified as vital resources to navigate the challenges of the early stages of teaching. Experienced teachers emphasized the importance of leadership development opportunities, including roles as department heads, curriculum coordinators, or teacher trainers. Access to advanced courses, conferences, and study opportunities was also deemed critical to prevent stagnation and keep up with evolving trends and methodologies in English language teaching. Professional development opportunities centered on technology integration were also highlighted to enhance student engagement and learning outcomes. Overall, this study underscores the necessity of ongoing professional development across all career stages to ensure English teachers remain motivated, effective, and equipped to provide the best possible learning experiences for their students.